Japanese Pan-Asianism and the Philippines from the late nineteenth century to the end of world war II going to the Philippines is like coming home - Matthiessen, Sven (Brill's Japanese studies library, 2016)
"Examines the development of Japanese Pan-Asianism and the perception of the Philippines within this ideology. Due to the archipelago's previous colonization by Spain and the US, the Philippines was a special case among the Japanese occupied territories during the war. Matthiessen convincingly proves that the widespread pro-Americanism among the Philippine population made it impossible for Japanese administrators to implement a pan-Asianist ideology that centred on a return to Asian values"--